2020
DOI: 10.1021/acs.bioconjchem.0c00146
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Platform to Identify Antibody Conjugation Sites from Antibody–Drug Conjugate Libraries

Abstract: Antibody–drug conjugates (ADCs) are a therapeutic modality that traditionally enable the targeted delivery of highly potent cytotoxic agents to specific cells such as tumor cells. More recently, antibodies have been used to deliver molecules such as antibiotics, antigens, and adjuvants to bacteria or specific immune cell subsets. Site-directed mutagenesis of proteins permits more precise control over the site and stoichiometry of their conjugation, giving rise to homogeneous chemically defined ADCs. Identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The binding and reactive properties of clones identified in this study highlight the potentially broad scope of antibody modifications achievable with additional chemical functionalization. However, we recognize that there are numerous effective bioconjugation strategies that may be applied to prepare chemically diversified antibodies, including thiol modification strategies, 22,78 enzymatic modification strategies, 23 or emerging conjugation reactions at other canonical amino acids. 79,80 In this regard, the simple synthetic antibodies and characterization strategies elucidated in this work could facilitate side-by-side evaluations of multiple chemical modification strategies.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The binding and reactive properties of clones identified in this study highlight the potentially broad scope of antibody modifications achievable with additional chemical functionalization. However, we recognize that there are numerous effective bioconjugation strategies that may be applied to prepare chemically diversified antibodies, including thiol modification strategies, 22,78 enzymatic modification strategies, 23 or emerging conjugation reactions at other canonical amino acids. 79,80 In this regard, the simple synthetic antibodies and characterization strategies elucidated in this work could facilitate side-by-side evaluations of multiple chemical modification strategies.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…32,[35][36][37][38] Numerous approaches to antibody chemical diversification have been explored extensively within the context of antibody-drug conjugates (ADCs). [39][40][41][42][43][44][45][46] However, most ADC development strategies focus on modification sites located in antibody constant regions that have little or no effect on antigen binding; [46][47][48][49][50][51][52] the result is modular addition of new chemistries that leave antibody binding function unchanged. In contrast, only sparse studies exist that examine the effects of adding chemical functionality near antibody complementarity determining regions (CDRs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent screening led to the identification of several genetic variants containing the engineered glutamine tag that permits coupling of linker payload into the C’E loop where N -glycosylation occurs. 18 Using these constructs, we tested the impact of loading drug linkers on the thermal stability of glycosylated and aglycosylated antibodies. In general, conjugating the drug to a glycosylated antibody resulted in decreased thermal stability, whereas attaching the drug to an aglycosylated antibody led to an increased melting temperature for some of the constructs.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Yamazoe et al have recently reported a high-throughput protocol for assisting the determination of optimal locations for drug conjugation. 290 mTG-conjugation was utilised to generate a library of ADCs from a pool of mutated antibodies, which were analysed and validated via MS. The screening allowed for several new tags and sites to be identified and may prove to be an important tool for future development and optimisation of homogeneous ADCs.…”
Section: Transglutaminasementioning
confidence: 99%